Role of pre-operative counseling with NSQIP surgical risk calculator in the surgical patients - Bikash Khadka; Apurb Sharma; Prajjwal Raj Bhattarai; Bijay Rayamajhi; Hemant Adhikari (Surgery Open Science, 2024)
Introduction: Patient satisfaction is important tool to monitor health care performance and quality of health plans, emphasizing effective counseling and consent processes. The objective of the study is to assess patient satisfaction and anxiety with the use of NSQIP surgical risk calculator in comparison to standardized questionnaires. Methodology: This is an interventional prospective randomized study. Difference in patient satisfaction is assessed by a 7-point Likert scale and anxiety assessment by 5-point Likert scale of Amsterdam Preoperative Anxiety and Information Scale (APAIS) questionnaire written in Nepalese. Satisfaction scores were compared using analysis of variance (ANOVA), or the Kruskal-Wallis test. P- value <0.05 was considered statistically significant. Results: Satisfaction score regarding comfort during counseling and consent process was similar with and without use of NSQIP surgical risk calculator (83.3 % and 76.9 %, respectively). Satisfaction score regarding plan of anesthesia was 63.33 % with the use of NSQIP and 53.8 % without NSQIP tool. 30.76 % of patients with high school education developed negative feelings following counseling when NSQIP tool was not used (p value 0.002). NSQIP usage increased anxiety about anesthesia and surgery and led to higher continual thinking about the procedure.Duration of counseling was 12 min with NSQIP tool use in comparison to 9.67 min following conventional counseling (p value 0.047). Conclusion: NSQIP surgical risk calculator is a reliable tool that can be used alongside conventional methods during preoperative period for decision-making and counseling with similar satisfaction scores but a higher incidence of anxiety and continual thinking about procedures.